How Leader Alignment of Words and Deeds Affects Followers: A Meta-analysis of Behavioral Integrity Research - Simons, Tony (Journal of business ethics, 2015)
Substantial research examines the follower consequences of leader (mis)alignment of words and deeds, but no research has quantitatively reviewed these effects. This study examines extant research on behavioral integrity (BI) and contrasts it with two other constructs that focus on (mis)alignment: moral integrity and psychological contract breaches. We compare effect sizes between the three constructs, and find that BI has stronger effects on trust, in-role task performance and citizenship behavior (OCB) than moral integrity and stronger effects on commitment and OCB than psychological contract breach. These stronger attitudinal consequences run counter to our initial expectations, but they provide evidence of important conceptual distinctions and mechanisms that we articulate. BI theory suggests that BI’s greater performance impact is due to the notion that BI affects communication clarity in addition to attitudes. Results of meta-analytic structural equation modeling are consistent with this proposed dual path of BI’s impact. We highlight avenues for future research on BI and discuss how our findings inform the broader research on leader (mis)alignment.